Next generation sequencing misguided the clinical interpretation of the PRSS1 variant in pediatric pancreatitis: a case report - Liu, Yao; Miao, Hongjun; Zhang, Qin (Frontiers in Pediatrics, 2025)
Next-generation sequencing (NGS), known as massively parallel sequencing, is transitioning from research tools to a clinical diagnostic methods. Whole-exome sequencing (WES), a specific applications of NGS, has emerged as a valuablefirst-line diagnostic tool for patients with rare diseases and shows promise as aas a comprehensive approach for assessing the prevalence of hereditary pancreatitis. Herein, we present a pediatric case that highlights the pitfalls of false-positive missense variants calls in the PRSS1 gene when using NGS. The patient was ultimately diagnosed with valproic acid-induced acute pancreatitis. Our findings emphasize that relying solely on WES data in epidemiological studies of hereditary pancreatitis might introduce bias, given the difficulties in accurately detecting variants within highly homologous genomic regions.